The Role of Family Education in Improving Religion and Moral Values in Early Childhood - Meilida Eka Sari; Dwi Noviana Komsi; Sri Yanti; Hecksa Manora (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
This study explores the family education program's role in enhancing children's religious and moral values at Hamizan Lubuklinggau Kindergarten. Employing a qualitative approach, data collection involved observation, documentation, and interviews. The analysis highlighted six family education programs, including socialization activities, parenting classes, parental involvement, joint events, consultation days, and home visits. The study identifies family education's five-fold role: promoter, inspirer, motivator, guide, and role model. However, challenges surfaced, such as limited interaction time due to parental and economic commitments, communication difficulties, and external influences like technology and peer interactions. In conclusion, the family education program significantly contributes to children's moral and religious development, yet addressing challenges, like time constraints and technology's impact, is vital for sustained efficacy. This research sheds light on the pivotal role of family education in nurturing children's values, urging continued efforts to overcome hindrances and optimize its impact.